Low-host double MDA workflow for uncultured ASFV positive blood and serum sample sequencing - Zhang, Chengjun; Cheng, Tangyu; Li, Dongfan; Yu, Xuexiang; Chen, Fangzhou; He, Qigai (Frontiers in Veterinary Science, 2022)
African swine fever (ASF) is a highly lethal and contagious disease caused by African swine fever virus (ASFV). Whole-genome sequencing of ASFV is necessary to study its mutation, recombination, and trace its transmission. Uncultured samples have a considerable amount of background DNA which causes waste of sequencing throughput, storage space, and computing resources. Sequencing methods attempted for uncultured samples have various drawbacks. In this study, we improved C18 spacer MDA (Multiple Displacement Amplification) combined host DNA exhaustion strategy to remove background DNA and fit NGS and TGS sequencing. Using this workflow, we successfully sequenced two uncultured ASFV positive samples. The results show that this method can significantly reduce the percentage of background DNA. We also developed software that can perform real-time basecall and analyses in set intervals of ASFV TGS sequencing reads on a cloud server.